Identify and analyze the Diversity of Ant in Indonesia, Diversity of Ants at the Universitas Sumatera Utara and Diversity of Ants at The Universitas Andalas - Juriyah Astika Dewi (International Journal of Ecophysiology, 2022)
One of the diversity of subfamily level ants is Myrmicinae. Myrmicinae are distributed throughout the world in all major habitats except ecosystem areas with low diversity indicating pressure that will affect ecosystem quality. The types of ants obtained from the location of the USU campus found 9 species consisting of 5 subfamilies as follows: Paracidris sp. Paedalgus sp. Solenopsis sp. Oligomyrmex sp. The total ant diversity index (H') on the USU campus included moderate diversity (H') 1.25, the genus with the highest distribution frequency at all research sites was Solenopsis sp, namely 50% Oligomyrmex sp, a genus with a low distribution frequency of 15%. The results of research at Andalas University, the total number of species accumulated in this study was the highest among other studies reported from Sumatra. The Quadra protocol is the standard method for rapid research of ants. Collecting the prominent number of ant species listed in this study is also effective for detecting frequent and abundant ant species. The analysis of the data obtained shows that it is possible to record more species of ants considering that field exploration continues